Human Ontology in Critical Pedagogy and Its Implications for Multicultural Islamic Education - Ahmad Sulaiman; Siti Azizah; Rahmat Hidayatullah (Universitas Muhammadiyah Malang, 2023)
Plurality is an undeniable social reality. But unfortunately, lately there are many phenomena that show tension due to differences in identity. In this article, this is understood as the result of education that is not based on a correct view of human’s true nature. What happens is that education treats humans like programmed machines that can swallow all facts according to the interests of the authorities or elites. This condition is very dangerous because it negates students' ability to understand and reflect on diversity. So that pluralism is only understood as knowledge in theory, not as a reality that occurs every day. Horizontal conflicts are also very prone to occur due to the lack of individual acceptance of multiple realities. Because of this, it is deemed necessary to reorient education so that education is based on the view of the whole human being and enables students to be more adaptive in responding to the reality of plurality. In this article, this effort is made by integrating human ontology of critical pedagogy with the multicultural Islamic religious education. The focus on multicultural Islamic religious education is based on the consideration that religion is an important identity for a person and that Islam is the religion embraced by the majority of the Indonesian population. It is shown here that critical pedagogy understands human nature as an independent, conscious and egalitarian being. This ontology inspires a learning methodology that encourages dialogue, mutual understanding, critical awareness, and produces actions to overcome injustices.